2017
DOI: 10.1515/saeb-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spokesperson’s Gender and Advertising Color Temperature in a Framework of Advertising Effectiveness

Abstract: Advertising spokesperson is one of the undeniably important factors affecting advertising effectiveness. However, advertising spokesperson has to have some particular features to be effective. Various previous researches resulted in determination of different features of advertising spokesperson and their effectiveness; i.e. type of a spokesperson (celebrity vs. a regular person); gender and race of a spokesperson; etc. were found to have an impact on the spokesperson's effectiveness. However, the research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Depending on the tool used, we can get information on how consumers process advertising stimuli. For instance, EEG can be used to evaluate the effectiveness of advertising by measuring the brain activity within milliseconds (Vecchiato et al, 2011 ; Kong et al, 2013 ; Pileliene and Grigaliunaite, 2017b ). In particular, EEG oscillations, measured through the changes in spectral power of EEG for some certain frequency bands, and in specific brain regions, while investigating in the frequency domain, or, while investigating in the time domain by looking at the derivation of particular event-related potential (ERPs), can indicate a higher or lower level of attention/memory/engagement of participants for a different type of advertisements (e.g., movie trailers, anti-binge-drinking campaigns, Boksem and Smidts, 2015 ; Gountas et al, 2019 , see Table 3 ).…”
Section: Main Applications In Marketingmentioning
confidence: 99%
“…Depending on the tool used, we can get information on how consumers process advertising stimuli. For instance, EEG can be used to evaluate the effectiveness of advertising by measuring the brain activity within milliseconds (Vecchiato et al, 2011 ; Kong et al, 2013 ; Pileliene and Grigaliunaite, 2017b ). In particular, EEG oscillations, measured through the changes in spectral power of EEG for some certain frequency bands, and in specific brain regions, while investigating in the frequency domain, or, while investigating in the time domain by looking at the derivation of particular event-related potential (ERPs), can indicate a higher or lower level of attention/memory/engagement of participants for a different type of advertisements (e.g., movie trailers, anti-binge-drinking campaigns, Boksem and Smidts, 2015 ; Gountas et al, 2019 , see Table 3 ).…”
Section: Main Applications In Marketingmentioning
confidence: 99%
“…The findings of Oliveira and Giraldi [68] revealed that the well-known brand has a more substantial impact on visual attention than others. Pileliene and Grigaliunaite [9] used ET to measure the influence of the advertisement's color temperature on consumers' visual attention. The findings showed that the warm color has a more substantial impact on consumers' visual attention than the cool color, thereby, purchase intention.…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
“…At the same time, most consumers' behavior occurs subconsciously or unconscious [4]. Due to the high-competitive environment, many researchers and marketers tried to fill the gap in self-report methods by using neuroscience tools to study consumers' unconscious and subconscious responses toward stimuli such as ads, brands, and products [9]. Consequently, marketers have been adopting neuroscience tools to accomplish marketing excellence (e.g., ads) because advertising is an important channel to communicate with current customers and potential customers [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has investigated the influence of color temperature of ad and the gender of spokesperson on the advertising effectiveness. Their findings suggested that the warm color temperature attracts more visual attention to the advertisement, generating a positive implicit attitude to the advertisement and inducing the buying intentions of the advertised products compared with cool color temperature advertisements whether the spokesperson's female or male celebrity (Pileliene & Grigaliunaite, 2017). Therefore, the color temperature impacts the effectiveness of the advertising spokesperson and advertising effectiveness.…”
Section: Eye-trackingmentioning
confidence: 99%